Mental health and post-traumatic stress symptoms related to combat in soldiers at Phramongkutklao Hospital. - Penglong, K.; Lalitanantpong, D. (Chulalongkorn Medical Journal, 2023)
Background : This is a study of post traumatic stress at a Thai military hospital in soldiers that experienced combat related mental trauma. Objective : To study mental health and so-called post-traumatic stress symptoms and associated factors related to combat in soldiers at Phramongkutklao Hospital. Design : Cross sectional descriptive study. Setting : Phramongkutklao Hospital, Bangkok. Materials and Methods : Data were collected from 108 soldiers traumatized physically or mentally in combat and admitted at Phramongkutklao Hospital. Self-report questionnaire included: 1) Personal information; 2) Symptom Distress Checklist 90 (SCL.90); 3) General Health Questionnaire Plus-R (GHQ 12 Plus-R) Part 2 PTSD Screening Test. Univariate analysis was used to determine the associated factors with mental health and post-traumatic stress symptoms. Results : Most soldiers in combat (73.1%) had mental health problems; 50.0 % also suffered from obsessive – compulsive symptoms. From Univariate analysis, the factors associated with mental health problems; were injury while performing field missions with wounds. And most of the soldiers in combat (77.8 %) did not have post-traumatic stress symptoms: the factors associated with post-traumatic stress symptoms; were age, pre-existing marital status, level of education, and injury by being shot while on official missions. Conclusion : Most soldiers wounded from combat had mental health problems but not typical post-traumatic stress symptoms.